The African Canadian Legal Odyssey - BARRINGTON WALKER (University of Toronto Press, 2013)
This introduction, in the first Osgoode Society collection and reader on the history of Blacks and the law in Canada, makes two main arguments. First, the social history of Blacks in Canada is inextricably bound to the question of law – more so than any other historically disenfranchised group in Canada, save for its First Nations peoples. Second, the profoundly legal dimension of Black Canadian social history is a consequence of the era of European empire and slavery where questions of Blacks’ legal and citizenship status, the nature and quality of their freedom, and even their very humanity often hinged upon questions of law. The law had a central role in defining Black Canadian life in the slavery and the post-slavery eras, but this role was often ambiguous and changed over time. Slavery was legally supported in one of two ways: through positive law, and more passively through the recognition of the customary use of slaves (including the recognition of the property right that slave-owners held in their slaves). In the post-emancipation period (after 1833) Blacks enjoyed legal freedom; and yet, during this period the law’s role in their lives was ambiguous and the quality of the freedoms they enjoyed was limited. While anti-Black discrimination was not supported by positive law in Canada, throughout Canadian history the law tended to passively support white supremacy by accepting the conditions that allowed it to thrive. Ambiguity thus lies at the heart of the Black Canadian legal odyssey,and this introduction explores the elements and the implications of this ambiguity.